Do CITES trade restrictions work? Some evidence from the markets for sawfish trophies - Gómez-Rodríguez Santiago; Wilson James R. (Aquatic Living Resources, 2022)
The durability of animal parts that are collected and traded as trophies has an impact on species sustainability, especially when animals are slow-growing, have low fecundity, or are particularly vulnerable to capture. CITES (the Convention on International Trade in Endangered Species of Wild Fauna and Flora), aims to control the trade of wild fauna and flora specifically by using trade restrictions as a policy option. However, specialists in international trade have advised against using trade restrictions to correct social cost issues. The reasons for this advice have to do with the unintended economic consequences of animals being placed on an endangered species list, coupled with the trade restrictions themselves. We focused on Pristis spp. (sawfish), a species in danger of extinction found in Appendix I of the CITES convention. An extensive search of sawfish saws for sale on the internet was performed during 2016 and 2017. A total of 174 observations of market prices were collected. We estimated several models linking prices to the size of the saw with other variables that might explain price variability using OLS regression, and which included data from both the original internet searches and additional variables, including a dummy variable which indicated the year in which the species group was placed in Appendix I. These models show that rather than slow down the extinction pathway for this species, CITES may have sped it up, as well as driving the sawfish trophy markets underground.